2017
DOI: 10.1021/acs.organomet.7b00258
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Amide Formation from the Dehydrogenative Coupling of Alcohols and Secondary Amines

Abstract: The five-coordinate iron(II) hydride complex ( iPr PNP)Fe(H)(CO) ( iPr PNP = N[CH 2 CH 2 (P i Pr 2 )] 2 ) selectively catalyzes the dehydrogenative intermolecular coupling of alcohols and secondary amines to form tertiary amides. This is the most productive base-metal catalyst for dehydrogenative amidation reported to date, in some cases achieving up to 600 turnovers. The catalyst works well for sterically undemanding amines and alcohols or cyclic substrates and is particularly effective in the synthesis of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 40 publications
2
54
0
Order By: Relevance
“…Impressive TONs were achieved for methanol. [103] Slightly better TONs and higher yields of product could be achieved by Milstein and coworkers using Mn-10 b. [104] Gauvin and co-workers showed that using Mn-16 alcohol can be converted into the corresponding ester via H 2 evolution (Scheme 13), including the synthesis of g-butyrolactone from 1,4-butanediol.…”
Section: Dehydrogenative Couplingmentioning
confidence: 99%
“…Impressive TONs were achieved for methanol. [103] Slightly better TONs and higher yields of product could be achieved by Milstein and coworkers using Mn-10 b. [104] Gauvin and co-workers showed that using Mn-16 alcohol can be converted into the corresponding ester via H 2 evolution (Scheme 13), including the synthesis of g-butyrolactone from 1,4-butanediol.…”
Section: Dehydrogenative Couplingmentioning
confidence: 99%
“…The dehydrogenative coupling of alcohols with amines can be performed with catalysts based on Re, Rh, Ru, Fe, and Mn, Scheme shows some representative examples. Complexes 16 a , 16 b , and 22 a show high activity, in particular with primary amines.…”
Section: Dehydrogenation Reactionsmentioning
confidence: 99%
“…[8,9] Beller and co-workers have reported the synthesis of various lactams from amino alcohols using an iron pincer catalyst. [11] However,w hile efficient with methanol, the catalyst showed poor catalytic activity with alcohols higher than methanol, such as ethanol or hexanol. [11] However,w hile efficient with methanol, the catalyst showed poor catalytic activity with alcohols higher than methanol, such as ethanol or hexanol.…”
mentioning
confidence: 99%